2020
DOI: 10.1111/jdv.16684
|View full text |Cite
|
Sign up to set email alerts
|

Practical recommendations for systemic treatment in psoriasis according to age, pregnancy, metabolic syndrome, mental health, psoriasis subtype and treatment history (BETA‐PSO: Belgian Evidence‐based Treatment Advice in Psoriasis; part 1)

Abstract: Background Impressive progress in new therapeutic options has been made for psoriasis. Treatments include topical steroids, phototherapy, conventional, synthetic disease-modifying drugs and an expanding list of biologics. Objective The primary objective of this work was to collect evidence for the creation of practice guidelines for systemic treatment of psoriasis (BETA-PSO: Belgian Evidence-based Treatment Advice in Psoriasis). Methods Evidence-based recommendations were formulated using a quasi-Delphi method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(48 citation statements)
references
References 78 publications
0
28
0
4
Order By: Relevance
“…Comorbidities could influence the treatment strategy (14). Figure 2 lists selected therapeutics for adult systemic psoriasis with comorbidities (74)(75)(76)(77). Treatment should be tailored to meet the needs of patients (Figure 2).…”
Section: Therapy For Psoriasismentioning
confidence: 99%
“…Comorbidities could influence the treatment strategy (14). Figure 2 lists selected therapeutics for adult systemic psoriasis with comorbidities (74)(75)(76)(77). Treatment should be tailored to meet the needs of patients (Figure 2).…”
Section: Therapy For Psoriasismentioning
confidence: 99%
“…Inclusion to such programmes elements specific for narrow professional groups may be beneficial. It is now a popular tendency to make specific recommendations for narrow subgroups of patients to increase its efficacy 20,21 . Our results may also be used in development of occupational skin diseases‐specific HRQoL instruments.…”
Section: Discussionmentioning
confidence: 73%
“…However, there are no conclusive data to enunciate meaningful clinical recommendations. Although some studies suggest that TNF-α inhibitors are associated with a decrease in insulin resistance, the study by Wu et al has shown no benefit with anti-TNF-α drugs in combination with methotrexate versus methotrexate alone on HbA1C or fasting blood glucose in psoriasis patients [ 130 , 131 , 132 , 133 ]. There is no evidence to show whether one of the listed drugs is efficacious compared with another in a patient with psoriasis and fatty liver disease [ 134 ].…”
Section: Discussionmentioning
confidence: 99%